1991
DOI: 10.1039/ft9918702173
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cations and sugars. Part 6.—Calorimetric method for simultaneous determination of the stability constant and enthalpy change for weak complexation

Abstract: A calorimetric method that allows simultaneous determination of both the association constant and the enthalpy change for weak complexation of a cation by a neutral ligand in water is presented. The theoretical and experimental aspects of the procedure are developed. The method involves the separation of the enthalpy of transfer of the electrolyte from water to an aqueous solution of the ligand into a specific contribution characterizing the interaction of the cation with the complexing site of the ligand and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Phone: (613) 564 2967, fax: (613) 564 6793, e-mail: Detse@UOTTAWA. ers have determined the stability constants for the case of Dribose (7)(8)(9). The value they find for ca2+-ribose in water is in excellent agreement with that determined electrochemically by using a liquid-membrane electrode selective to ca2+ ions (10) but much smaller than other reported values (6,(11)(12)(13).…”
Section: Introductionsupporting
confidence: 67%
“…Phone: (613) 564 2967, fax: (613) 564 6793, e-mail: Detse@UOTTAWA. ers have determined the stability constants for the case of Dribose (7)(8)(9). The value they find for ca2+-ribose in water is in excellent agreement with that determined electrochemically by using a liquid-membrane electrode selective to ca2+ ions (10) but much smaller than other reported values (6,(11)(12)(13).…”
Section: Introductionsupporting
confidence: 67%
“…Morel and co-workers [42][43][44][45][46][47][48][49], Wang and co-workers [50][51][52][53][54][55][56][57][58][59][60][61], and Hernandez-Luis et al [62,63] used the transfer functions approach and reported a very comprehensive set of data for the interaction parameters of sugars with several electrolytes.…”
Section: Empirical Virial Expansionsmentioning
confidence: 99%
“…7 and Table 5). This behaviour may be due to the possibility of complexation over and above ion formation where the cation, Mg 2 may affect sugar systems (Matiacevich et al, 2010;Morel-Desrosiers et al, 1991;Shimada and Saka, 2007;Philippe et al, 2003;Bailey and Carper, 1993). Interactions between sugars and alkaline earth metal halides, such as MgCl 2 and calcium chloride (CaCl 2 ), have been reported in a number of studies where a sugar-cation complex can form, the hydrated cation is able to coordinate with the oxygen atoms of the sugar molecule.…”
Section: Ternary Systems Of Electrolyte + Sugarmentioning
confidence: 95%
“…Here the electrolyte is responsible for dispersing the sugar molecules and thus creating an increase in osmosis. Sugar-H 2 O-Salt interactions have been reported in a number of studies, where NaCl and potassium chloride (KCl) have been found to weaken the H-bond network between sucrose and water (Morel-Desrosiers et al, 1991). Out of the two sugars with NaCl ternary systems, maltose generated the highest SF.…”
Section: Ternary Systems Of Electrolyte + Sugarmentioning
confidence: 96%